Behavior of GFRP strengthened masonry wall panels retrofitted with inner diagonal wrapping - Rathnasheela, P.T.; Senthil, R.; Thandavamoorthy, T.S. (Journal of Structural Engineering, 2025)
The paper presents details of experimental investigation relating to base impacted 1/3 scale model of brick masonry panel of size 1 m x 1m x 0.15 m strengthened with GFRP wrapping arranged in diagonal pattern by mounting it on a shock table especially designed and fabricated for this purpose and measuring the energy absorption and accelerations at its base, middle and top. Based on the experimental investigation, the failure pattern and energy dissipation capacity of the masonry panels with and without diagonally GFRP wrapped were determined. The frequency of GFRP strengthened panel was observed to be 17.5 Hz indicating that the wall panel had become stiff after strengthening.